La ecología y evolución del polimorfismo floral en Lithodora (Boraginaceae) - Ferrero, V. (Ecosistemas, 2009)
Ferrero, V. (2009). La ecología y evolución del polimorfismo floral en Lithodora (Boraginaceae). Ecosistemas 18(3):30-34.